Comparison Process of in-Patient Versus Out of Hospital Stroke Onset of Metricsina Community Primary Stroke Center - Chukwudelunzu, Felix E; Demaerschalk, Bart; Fugoso, Leonardo; Amadi, Emeka; Dexter, Donn; Gullicksrud, Angela; Hagen, Clinton (Medical Research and Its Applications Vol. 5, 2024)
Objective: The present study examines in-hospital stroke onset metrics and outcomes, quality of care, and mortality compared with out-of-hospital stroke in a single community-based primary stroke center. Background: In-hospital stroke vs OHS comparisons of demographic characteristics, hospital characteristics, immediate treatment with thrombolysis therapy, and mortality have been found to favor OHS cohorts in multiple studies. Patients and Methods: We performed a retrospective analysis of all patients for whom an IHS stroke alert occurred during admission to our hospital between January 1, 2013, and December 31, 2019. Time-sensitive stroke process metric data were collected for each incident stroke alert. The primary focus of interest was the time-sensitive stroke quality metrics. The secondary focus pertained to thrombolysis treatment or complications, and mortality. Descriptive and univariable statistical analyses were applied. Kruskal-Wallis and c2 tests were used to compare median values and categorical data between prespecified groups. The statistical significance was set at p<.05. Results: The out-of-hospital group reported a more favorable response to time-sensitive stroke process metrics than the in-hospital group, as measured by median stroke team response time (15.0 vs 26.0 minutes; P\(\le\).0001) and median head computed tomography scan completion time (12.0 vs 41.0 minutes; p<.0001). There was no difference in the stroke alert time between the 2 groups (14.0 vs 8.0 minutes; p .99). Longer hospital length of stay (4 vs 3 days; p.0001) and increased hospital mortality (19.3% vs 7.4%; p.001) were observed for the in-hospital group. The association between time-sensitive stroke process metrics and outcomes, such as hospital mortality and hospital length of stay, in the IHS cohort may be co-founded by higher baseline comorbidities, a higher risk of hospital complications, lower eligibility, and a higher number of contraindications for intravenous thrombolysis therapy and thrombectomy in the IHS cohort. Conclusions: It is revealed that the out-of-hospital groups' time-sensitive stroke process metrics and stroke outcome measures outperformed the in-hospital groups'. Enhancing time-sensitive stroke process indicators could lead to better outcomes for the stroke cohort receiving care in hospitals.